PATH-49. CLINICAL UTILITY OF PLASMA CELL-FREE DNA IN ADULT PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA – A PILOT PROSPECTIVE STUDY. (11th November 2019) - Bagley, Stephen; Nabavizadeh, Seyed; Mays, Jazmine; Till, Jacob; Yee, Stephanie; Ware, Jeffrey; Guiry, Samantha; Nasrallah, MacLean; Levy, Scott; Sarchiapone, Whitney; Hussain, Jasmin; Prior, Timothy; et al.
Abstract: BACKGROUND: Liquid biopsy has been not been widely utilized in patients with glioblastoma (GBM) compared to other solid tumors. However, the clinical utility of plasma cell-free DNA (cfDNA) in GBM has not been assessed prospectively or at the time of initial diagnosis. METHODS: We conducted a prospective cohort study of patients with newly diagnosed GBM. Whole blood was collected in Streck® tubes at baseline prior to initial surgical resection and longitudinally during the course of adjuvant chemoradiotherapy. Plasma cfDNA concentration (ng/mL) was quantified by qPCR for a 115 bp amplicon of the human ALU repeat element, correlated with radiographic tumor burden by volumetry at multiple time points using Spearman rank correlation, and assessed for its impact on progression-free (PFS) and overall survival (OS) by Cox regression. RESULTS: Prior to initial resection, GBM patients (N=42) had higher plasma cfDNA concentration compared to age-matched healthy controls (N=42) (mean 13.43 vs. 6.70 ng/mL, p< 0.001). Plasma cfDNA concentration was correlated with radiographic tumor burden on subjects' first post-radiation MRI scan (r=0.77, p=0.003) and tended to rise prior to or concurrently with radiographic tumor progression. Pre-operative plasma cfDNA concentration above the mean (>13.4 ng/mL) was associated with inferior PFS (median 4.9 vs. 9.5 months, p=0.038) and OS (median 8.9 vs. 14.8 months, p=0.078). The impact on PFS persisted after adjusting for age, extent of resection, performance status, MGMT promoter methylation, and IDH1/2 mutational status (HR 2.48, 95% CI 1.1–6.1, p=0.046). CONCLUSIONS: Plasma cfDNA may be an effective prognostic tool and noninvasive surrogate of tumor burden in newly diagnosed GBM. Tumor tissue samples from our cohort have been subjected to targeted next generation sequencing (NGS), and baseline plasma samples have been sent to Guardant Health for NGS. Plasma NGS results and concordance with matched tissue NGS will be included at time of presentation.